Accelerating a technology commercialization: With a discussion on the relation between technology transfer efficiency and open innovation - Wahyudi Sutopo; Rina Wiji Astuti; Retno Tanding Suryandari (Journal of Open Innovation: Technology, Market, and Complexity, 2019)
Commercialization strategy is an all-encompassing plan that organizes technology transfer office goals to commercialize a university's technologies. Measurement strategy requires feasible variables that make up those goals. This strategy also ensures that all variables that are important in measuring contribute to the larger goals. A useful way to assess and explain the effectiveness of the technology transfer office (TTO) of universities is to model this within a production function/frontier framework. Such a production function is typically estimated econometrically. This study presents evidence on the relative efficiency of research commercialization in the university through the data envelopment analysis (DEA) model. The implication of the DEA efficiency result is to derive the efficiency level of the TTO's strategy from the observed performance. It also helps in identifying the benchmarking of other TTOs, which would be valuable information for improving their new technology commercialization strategy. In detail, a benchmark is provided to improve the weakness of strategy and resource allocation of a poorly performing TTO. The proposed matrix of indicators is an exploit of how performance could be measured within the decision-making units that have been chosen. By introducing the measure to commercialization strategy framework the development of technology transfer offices policies are considered.
Keywords: 650; data envelopment analysis (DEA); efficiency strategy; performance measurement; technology commercialization; technology transfer office (TTO)